Tests on high-performance aerated concrete with a lower density. (15th January 2015) - Yang, Keun-Hyeok; Lee, Kyung-Ho
Highlights: This study developed high-performance aerated concrete to replace AAC block. Valuable data for high-strength aerated concrete with a lower density was provided. Prediction models for the various properties of such concrete were proposed. The effect of foaming volume rate on the properties of such concrete was ascertained. Abstract: The present study tested 16 concrete mixes to develop a high-performance aerated concrete without using high-pressure steam curing processes, as an alternative to autoclaved aerated concrete (AAC) blocks. To achieve high-strength gains, particularly at an early age, for aerated concrete under an air curing environment, the binder and chemical agent were specially contrived as follows: The loss on ignition of ordinary Portland cement was controlled to 1.5% and 3% anhydrous gypsum was then added; and the content of polyethylene glycol alkylether in a polycarboxylate-based water-reducing agent was modified to 28%. Furthermore, a foaming agent based on a protein-hydrolization with enzymatic active components was used to generate independently closed pores during concrete mixing. The test parameters investigated were the foaming volume rate ( Vf ) of the preformed foam, water-to-binder ratio ( W / B ), and unit binder content ( B ). The qualities of the developed high-performance aerated concrete were compared with the minimum requirements specified in ASTM C 1693 for AAC and with data of existing conventional aerated concrete. Prediction models for dry density, compressive strength, stress–strain relationship, and thermal conductivity of aerated concrete were formulated from the regression analyses of the test data. All concrete mixes investigated displayed enhanced workability and defoaming resistance, achieving self-compactability performance. Furthermore, the measured mechanical properties prove that the developed high-performance aerated concrete has considerable potential for practical application when B is approximately 550 kg/m 3 and when W / B ranges between 30% and 25%, at which it fulfils the minimum requirement for class AAC-4 of ASTM C 1693.